The Unanimity of Cultural Traditions of Bharat (India) with South East Asian Countries: A Saga of inclusivity and Universality - Sharma, Shasanka Shekhar; Choudhury, Subhajit (Journal of Indian Studies (இந்திய ஆய்விதழ்), 2025)
The paper introduces the history of movement of various communities during the reigns of several kings in Uttar Purbo Bharat. The settlement of communities in those areas gave birth to a new concept of livelihood. The livelihood changed, along with the way of living. This marked the beginning of a new culture and, in turn, a holistic Sanskriti. Typically, the whole North Eastern Region (Uttar Purbo Bharat) before the division of Bharat (India) and precisely before the 18th century A.D., there were many more changes with regard to religion. Similarly, it would be pertinent to mention that the Pragjyotishpur was the conglomeration of three religions- Hindu, Jain and Budha, as per excavations in Surya pahar (hill) now in the Goalpara District of Assam in India. During this time, Indian kings traveled to many places, from Myanmar to Indonesia and to Ankorbhat, Laos, Malaysia, Bangladesh, Sri Lanka etc. these far-reaching places from Bharat led to a study to know whether there are any similarities of Folk culture and traditions among Uttar Purbo Bharat and South East Asian Countries. Initially, the folk tradition of the communities of Uttar Purbo Bharat were narrated. Then, the various communities of selected countries were briefly mentioned after considering almost all the facets of their traditions. The authors collected both primary and secondary data from Uttar Purbo Bharat and Countries under study of South East Asia. The authors collected data through interviews during his visit to these countries. Observation through participation and historical research method were followed throughout the investigation and findings of the study. Kertas kerja ini memperkenalkan sejarah perpindahan pelbagai komuniti semasa pemerintahan beberapa raja di Uttar Purbo Bharat. Penempatan komuniti di kawasan-kawasan tersebut melahirkan konsep baru mata pencarian. Mata pencarian berubah, bersama dengan cara hidup. Ini menandakan permulaan budaya baru dan seterusnya, Sanskriti yang holistik. Secara amnya, seluruh Wilayah Timur Laut (Uttar Purbo Bharat) sebelum pembahagian Bharat (India) dan tepatnya sebelum abad ke-18 Masihi, terdapat lebih banyak perubahan berkenaan agama. Begitu juga, adalah wajar untuk menyebut bahawa Pragjyotishpur merupakan gabungan tiga agama - Hindu, Jain dan Buddha, mengikut penggalian di Surya Pahar (bukit) yang kini terletak di Daerah Goalpara, Assam di India. Pada masa ini, raja-raja India mengembara ke banyak tempat, dari Myanmar ke Indonesia dan ke Angkor Wat, Laos, Malaysia, Bangladesh, Sri Lanka dan sebagainya. Tempat-tempat yang jauh dari Bharat ini membawa kepada kajian untuk mengetahui sama ada terdapat sebarang persamaan budaya rakyat dan tradisi antara Uttar Purbo Bharat dan Negara-negara Asia Tenggara. Pada mulanya, tradisi rakyat komuniti-komuniti Uttar Purbo Bharat diceritakan. Kemudian, pelbagai komuniti dari negara-negara terpilih disebut secara ringkas selepas mempertimbangkan hampir semua aspek tradisi mereka. Penulis mengumpul data primer dan sekunder dari Uttar Purbo Bharat dan negara-negara Asia Tenggara yang dikaji. Penulis mengumpul data melalui temu bual semasa lawatan mereka ke negara-negara ini. Pemerhatian melalui penyertaan dan kaedah penyelidikan sejarah telah diikuti sepanjang penyiasatan dan penemuan kajian.